Pengaruh Capital Intensity dan Komisaris Independen terhadap Penghindaran Pajak dengan Ukuran Perusahaan sebagai Variabel Moderasi - Khairun Nabila; Andi Kartika (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this study was to determine the effect of capital intensity and independent commissioners on tax avoidance with firm size as a moderating variable. The type of data used in this research is secondary data, this research data was obtained from the 2017-2021 Financial Report and Annual Report. The population used in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange for the 2017-2021 period. The sampling method used was purposive sampling, where the total sample for 5 years was 100 companies. The results of this study indicate that Capital Intensity and Independent Commissioners have a significant negative effect on Tax Avoidance, and Company Size is able to strengthen Capital Intensity and Independent Commissioners on Tax Avoidance.